Vertical Articulation and Content Relevance of the Senior High School Economics Curriculum: Case of Ghana - Acquah, Bernard Yaw Sekyi; Owusu, Anthony Akwesi (Asian Journal of Education and Training, 2021)
The school curriculum is often the formal document designed for teachers to treat topics that allow for the impartation of knowledge and the development of competencies that prepare students for further studies. Achieving this depends mainly on its content structure and sequencing. The aim of this study is two-fold: to find the extent of vertical articulation of topics in the economics syllabus that makes it possible for the syllabus to achieve its purpose of preparing students for further studies; and to explore the extent to which the syllabus is up-to-date and relevant in dealing with current economic issues. Document analysis was used to analyse the syllabus, while eight (8) service teachers purposively selected were interviewed. The study found that the SHS economics curriculum lacked vertical content articulation regarding the learning competencies for Forms 1 to 3. Also, the interviews revealed that the curriculum is not up-to-date though relevant since many evolving economic concepts have not been captured. The study supports the call for curriculum change and alignment of content to improve its vertical articulation and coherence and its currency and relevance in helping to equip students with the requisite knowledge and fundamental economic tools for their daily survival.